2020
DOI: 10.1039/d0nr02527e
|View full text |Cite
|
Sign up to set email alerts
|

Ru and RuOxdecorated carbon nitride for efficient ammonia photosynthesis

Abstract: A ternary heterostructure Ru/RuO2/g-C3N4 was designed for ammonia photosynthesis under visible light irradiation, which exhibited 6 times higher activity with excellent stability than the pristine g-C3N4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(75 citation statements)
references
References 40 publications
6
69
0
Order By: Relevance
“…The derived de‐convolution envisages that the 284.9 and 281.6 eV core peak corresponds to the Ru 3d 3/2 and 3d 5/2 , respectively 28 . In addition, RuO x ‐related XPS peaks at 286.8 and 286.1 eV (Ru 3d 3/2 ) and 283.8 and 282.5 eV (Ru 3d 5/2 ) were attributed to the interaction with NGO and Co 3 O 4 in the composite 29 . The XPS C 1s region profile (Figure 6C) revealed peaks at 281.9 eV (CC), COC (285.5), and OC═O (288.5) eV.…”
Section: Resultsmentioning
confidence: 93%
“…The derived de‐convolution envisages that the 284.9 and 281.6 eV core peak corresponds to the Ru 3d 3/2 and 3d 5/2 , respectively 28 . In addition, RuO x ‐related XPS peaks at 286.8 and 286.1 eV (Ru 3d 3/2 ) and 283.8 and 282.5 eV (Ru 3d 5/2 ) were attributed to the interaction with NGO and Co 3 O 4 in the composite 29 . The XPS C 1s region profile (Figure 6C) revealed peaks at 281.9 eV (CC), COC (285.5), and OC═O (288.5) eV.…”
Section: Resultsmentioning
confidence: 93%
“…Wang et al reported a heterojunction photocatalyst composed of Ru, RuO 2 and g-C 3 N 4 . 33 Under light irradiation, electrons in g-C 3 N 4 transition from the valence band to the conduction band and can be easily captured by Ru. Finally, the electrons are transferred to the π* antibond orbital of the nitrogen molecule to promote the cleavage and activation of the nitrogen-nitrogen triple bond.…”
Section: Noble Metal-modified Photocatalysts For Ammonia Synthesismentioning
confidence: 99%
“…23,[31][32][33][34][35][36][37][38][39][40][54][55][56][57][64][65][66][67][68][69][70][71] The interface modulations, including the modification with cocatalysts and semiconductors, greatly affect the charge transfer and separation efficiency. [89][90][91][92][93][94][95][96][97][98][99][100][101][109][110][111] We will discuss these factors one by one below. In order to provide an intuitively systematic comparison for photocatalytic N2 reduction system, we list photocatalysts, reactants, NH3 production rate, in particular apparent quantum efficiency and detection method as shown in Table 1.…”
Section: Strategies To Improve Photocatalytic Efficiencymentioning
confidence: 99%
“…Such significant improvement in photocatalytic NH3 synthesis for Ru/RuO2/g-C3N4 was not only because of Ru and RuO2 acting as cocatalysts to promote electrons and holes transfer respectively, but also taking advantage of Ru for N2 chemisorption and activation. 109 Besides that, carbon-based materials especially graphene is also often used as cocatalysts to prevent the photoinduced electron-hole recombination and promote the electrons transfer due to its prominent electrical conductivity. 110,111 For instance, a Fe modified threedimensional graphene (Fe@graphene) photocatalyst was reported for the NH3 production.…”
Section: Interfacial Modulation Cocatalysts Loadingmentioning
confidence: 99%